Theileria parva (Muguga) infects bovine T-lymphocytes in vivo and induces coexpression of BoT4 and BoT8 - Emery, D.L.; MacHugh, Niall D.; Morrison, W. Ivan (Wiley, 1988)
Summary During the course of a lethal infection with Theileria parva (Muguga), the surface phenotypes of efferent lymphatic lymphocytes (ELL) were analysed to determine whether the parasite preferentially infected any particular subpopulation of cells. In the second week of infection, when the proportion of lymphoblasts and parasitized cells increased to 50% of the total ELL, > 99% of infected cells expressed T‐lymphocyte markers including both BoT4 and BoT8. From day 10, a population of T‐lymphocytes coexpressing BoT4 and BoT8 appeared in ELL, reaching 33% by day 14. Similar changes were observed in peripheral blood mononuclear cells (PBM) and lymph node cells (LNC). Analysis of ELL sorted into populations differing on the basis of expression of BoT4 and BoT8, revealed a higher level of parasitosis in the BoT4+ and BoT8+ lymphocytes than in the BoT4+ BoT8− or BoT4− BoT8+ populations. For comparison, the phenotypes of 28 cloned cell lines, obtained by infection of PBM with sporozoites in vitro, were examined. All of these clones exhibited T‐cell markers. Nine of the clones expressed both BoT4 and BoT8; within each of these lines, BoT4 was expressed on all cells, whereas BoT8 was expressed at variable concentrations on 20‐70% of cells. That BoT4+ cells were induced by T. parva (Muguga) to coexpress BoT8 was demonstrated directly by the finding that a BoT4+ BoT8− T‐cell clone expressed BoT8 following infection with the parasite.